Bedaquiline, moxifloxacin, pretomanid, and pyrazinamide during the first 8 weeks of treatment of patients with drug-susceptible or drug-resistant pulmonary tuberculosis: a multicentre, open-label, partially randomised, phase 2b trial - Tweed, Conor D (Lancet Respir Med, 2019)
BACKGROUND: New anti-tuberculosis regimens that are shorter, simpler, and less toxic than those that are currently available are needed as part of the global effort to address the tuberculosis epidemic. We aimed to investigate the bactericidal activity and safety profile of combinations of bedaquiline, pretomanid, moxifloxacin, and pyrazinamide in the first 8 weeks of treatment of pulmonary tuberculosis. METHODS: In this multicentre, open-label, partially randomised, phase 2b trial, we prospectively recruited patients with drug-susceptible or rifampicin-resistant pulmonary tuberculosis from seven sites in South Africa, two in Tanzania, and one in Uganda. Patients aged 18 years or older with sputum smear grade 1+ or higher were eligible for enrolment, and a molecular assay (GeneXpert or MTBDRplus) was used to confirm the diagnosis of tuberculosis and to distinguish between drug-susceptible and rifampicin-resistant tuberculosis. Patients who were HIV positive with a baseline CD4 cell count of less than 100 cells per uL were excluded. Patients with drug-susceptible tuberculosis were randomly assigned (1:1:1) using numbered treatment packs with sequential allocation by the pharmacist to receive 56 days of treatment with standard tuberculosis therapy (oral isoniazid, rifampicin, pyrazinamide, and ethambutol; HRZE), or pretomanid (oral 200 mg daily) and pyrazinamide (oral 1500 mg daily) with either oral bedaquiline 400 mg daily on days 1–14 then 200 mg three times per week (B(load)PaZ) or oral bedaquiline 200 mg daily (B(200)PaZ). Patients with rifampicin-resistant tuberculosis received 56 days of the B(200)PaZ regimen plus moxifloxacin 400 mg daily (BPaMZ). All treatment groups were open label, and randomisation was not stratified. Patients, trial investigators and staff, pharmacists or dispensers, laboratory staff (with the exception of the mycobacteriology laboratory staff), sponsor staff, and applicable contract research organisations were not masked. The primary efficacy outcome was daily percentage change in time to sputum culture positivity (TTP) in liquid medium over days 0–56 in the drug-susceptible tuberculosis population, based on non-linear mixed-effects regression modelling of log(10) (TTP) over time. The efficacy analysis population contained patients who received at least one dose of medication and who had efficacy data available and had no major protocol violations. The safety population contained patients who received at least one dose of medication. This study is registered with ClinicalTrials.gov, NCT02193776, and all patients have completed follow-up. FINDINGS: Between Oct 24, 2014, and Dec 15, 2015, we enrolled 180 patients with drug-susceptible tuberculosis (59 were randomly assigned to B(load)PaZ, 60 to B(200)PaZ, and 61 to HRZE) and 60 patients with rifampicin-resistant tuberculosis. 57 patients in the B(load)PaZ group, 56 in the B(200)PaZ group, and 59 in the HRZE group were included in the primary analysis. B(200)PaZ produced the highest daily percentage change in TTP (5·17% [95% Bayesian credibility interval 4·61–5·77]), followed by B(load)PaZ (4·87% [4·31–5·47]) and HRZE group (4·04% [3·67–4·42]). The bactericidal activity in B(200)PaZ and B(load)PaZ groups versus that in the HRZE group was significantly different. Higher proportions of patients in the B(load)PaZ (six [10%] of 59) and B(200)PaZ (five [8%] of 60) groups discontinued the study drug than in the HRZE group (two [3%] of 61) because of adverse events. Liver enzyme elevations were the most common grade 3 or 4 adverse events and resulted in the withdrawal of ten patients (five [8%] in the B(load)PaZ group, three [5%] in the B(200)PaZ group, and two [3%] in the HRZE group). Serious treatment-related adverse events affected two (3%) patients in the B(load)PaZ group and one (2%) patient in the HRZE group. Seven (4%) patients with drug-susceptible tuberculosis died and four (7%) patients with rifampicin-resistant tuberculosis died. None of the deaths were considered to be related to treatment. INTERPRETATION: B(200)PaZ is a promising regimen to treat patients with drug-susceptible tuberculosis. The bactericidal activity of both these regimens suggests that they have the potential to shorten treatment, and the simplified dosing schedule of B(200)PaZ could improve treatment adherence in the field. However, these findings must be investigated further in a phase 3 trial assessing treatment outcomes. FUNDING: TB Alliance, UK Department for International Development, Bill & Melinda Gates Foundation, US Agency for International Development, Directorate General for International Cooperation of the Netherlands, Irish Aid, Australia Department of Foreign Affairs and Trade, and the Federal Ministry for Education and Research of Germany.